Intergeracionalidade da violência intrafamiliar: um estudo de casos múltiplos - Medeiros, Jaqueline Knupp (2022)
It is the role of caregivers and those responsible for children and adolescents to employ educational practices aligned with the needs of these segments, so that they can fulfill their role of educating them in the best possible way, free from any form of violence and exploitation. However, there are historical, psychological and relational issues over the families and that support the maintenance of uninterrupted cycles of violence between different generations. Intergenerationality of violence is understood as parental practices permeated by violation of rights and that were transmitted between generations of the same family. Based on these premises, this thesis had the main objective to investigate the configuration and the functioning system present in the childhood of adults who practiced violence against their children and adolescents. In the first chapter, the theoretical framework and definitions about intrafamily violence against children and adolescents were presented, as well as the concepts of intergenerationality and naturalization of violence, which are essential for understanding the cycle of coercive practices and violence used by parents and guardians. The second chapter refers to an empirical investigation, based on a qualitative approach and from a multiple case study. This study aimed to explore the family context of childhood of adults who used violence against their own children. As a secondary objective, the analysis explored how the normalization of intrafamily violence occurred and how intergenerational violence within the same family nucleus is perpetuated. The study, carried out in a Brazilian context, had the participation of three adults, of both sexes, who committed physical or psychological violence or were considered negligent in relation to their children's education. Data collection was carried out using the Interview on the Past of Parents (IAPP) and family genograms. The findings showed factors that contribute to the perpetuation of violence over generations and explain the difficulties in breaking the cycles of violence. Importantly, the results highlighted how the disciplinary practices used with their own children were reproductions of parenting models and related manifestations of violence that the participants themselves were exposed to in childhood. Based on these findings, the importance of psychosocial interventions that help family members to replace coercive parenting practices with healthier strategies is reiterated.